(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Machines manufactured in mechanical engineering operate under very diverse conditions. In this case, protective coatings, in addition to general factors, are subject to specific (special) effects, mostly aggressive factors. Therefore, the study of protective coatings is considered important.